Ontological Security, Existential Anxiety and Workplace Privacy - Brown, William S. (Journal of business ethics, 2000)
The relationship of workers to management has traditionally been one of control. However, the introduction of increasingly sophisticated technology as a means of supervision in the modern workplace has dramatically altered the contours of this relationship, giving workers much less privacy and making workers much more visible than previously possible. The purpose of this paper is to examine the current state of technological control of workers and how it has altered the relationship of worker to organization, through the impact upon self as perceived by the worker.